1975
DOI: 10.1111/j.1600-0765.1975.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of experimental neutropenia in dogs with chronic gingivitis

Abstract: The influence of a four day period of experimental neutropenia on the clinical state and the structural constituents of chronically inflamed gingiva has been studied in four beagle dogs. Neutropenia was induced by heterologous anti‐neutrophil serum. The effects on the gingiva were evaluated by Gingival Index (GI) and Gingival Exudate measurements and by morphometric analysis of various tissue components in sections from biopsies of buccal gingiva sampled on days 2, 3, and 4. Control biopsies were obtained befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
1

Year Published

1977
1977
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
3
11
1
Order By: Relevance
“…Observation of abundant PMN in the soft tissues contradicts the findings of previous studies of infrequent presence (Kyle & Linman 1970, Reichart & Domow 1978. Deasy et al 1980 or almost complete absence of PMN (Lampert & Fesseler 1975) in the periodontal soft tissues of chronic neutropenic patients, and of neutropenic dogs (Rylander et al 1975). Previous findings were based on light microscopy whereas the present biopsies were examined by TEM.…”
Section: Histopathologycontrasting
confidence: 68%
“…Observation of abundant PMN in the soft tissues contradicts the findings of previous studies of infrequent presence (Kyle & Linman 1970, Reichart & Domow 1978. Deasy et al 1980 or almost complete absence of PMN (Lampert & Fesseler 1975) in the periodontal soft tissues of chronic neutropenic patients, and of neutropenic dogs (Rylander et al 1975). Previous findings were based on light microscopy whereas the present biopsies were examined by TEM.…”
Section: Histopathologycontrasting
confidence: 68%
“…On the other hand, in experimentally induced neutropenia using heterologous anti-neutrophil serum in dogs, Rylander et al (1975) showed that in spite of the complete absence of PMN's from the gingiva, no direct bacterial invasion of the tissues occurred, while in the tissue no change except a relative increase in the numbers of plasma cells was observed. It seems, therefore, that the precise role of gingival sulcus PMN's in chronic inflammatory periodontal disease remains to be ascertained.…”
Section: Cellular Aspectsmentioning
confidence: 98%
“…Other systemic conditions identified as affecting the plaque-gingivitis relationship include neutropenia (Andrews et al 1965, Rylander et al 1975, Reichart & Dornow 1978, leukemia (Levin & Kennedy 1973, Bergmann et al 1992, and human immunodeficiency virus/ acquired immune deficiency syndrome (Glick et al 1990). Psychological stress, at least in adults (Deinzer et al 1998, Vanderas et al 1998), leads to heightened gingivitis expression.…”
Section: Other Systemic Factorsmentioning
confidence: 99%